Pengaruh Profitabilitas Terhadap Nilai Perusahaan dengan Struktur Modal Sebagai Variabel Intervening: (Studi Kasus Pada Perusahaan Yang Terdaftar Pada IDX 30) - Supandi, Ahmad; Goenawan, Yohanes August (JOURNAL INTELEKTUAL, 2023)
Introduction/Main Objectives: To determine the influence between Profitability, Company Value and Capital Structure in IDX30 Registered Companies for the 2018-2021 Period. Background Problems: The phenomenal growth of Price Book Value in the research locus shows that the data varies every year, this has a correlation with the increase in the company's net profit. Novelty: Retesting the same variables by previous researchers, because there are still research differences between one study and another. Research Methods: This research uses a descriptive quantitative approach using secondary data on fifteen (15) companies and the analysis used is path analysis. Finding/Results: From the research results, ROE does not have a significant effect on DER. The results of this study show that DER has no significant effect on PBV. The research results show that the direct influence value is greater than the indirect influence value. Conclusion: Companies can pay attention to factors that can influence increasing company value. If the company value increases, it is hoped that investors will be more interested in investing their funds and ultimately the welfare of shareholders can increase.